2020
DOI: 10.1007/s10668-020-01075-4
|View full text |Cite
|
Sign up to set email alerts
|

Lessons learned and questions raised during and post-COVID-19 anthropopause period in relation to the environment and climate

Abstract: In the first part, this work reports that during the global “anthropopause” period, that was imposed in March and April 2020 for limiting the spread of COVID-19, the concentrations of basic air pollutants over Europe were reduced by up to 70%. During May and June, the gradual lift of the stringent measures resulted in the recovery of these reductions with pollution concentrations approaching the levels before the lockdown by the end of June 2020. In the second part, this work examines the alleged correlations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 81 publications
2
5
0
Order By: Relevance
“…In general, it is important to note that when comparing the NO 2 and (PM 10 ) reductions during the lockdown, it is important to note that rural background concentrations of atmospheric particulate originate from non-urban sources thereby their reductions are generally less than NO 2 , which is an urban pollutant. Similar results were reported in another study conducted in Europe (Zerefos et al, 2020 ).…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…In general, it is important to note that when comparing the NO 2 and (PM 10 ) reductions during the lockdown, it is important to note that rural background concentrations of atmospheric particulate originate from non-urban sources thereby their reductions are generally less than NO 2 , which is an urban pollutant. Similar results were reported in another study conducted in Europe (Zerefos et al, 2020 ).…”
Section: Resultssupporting
confidence: 92%
“…In this context, it is important to mention that in general important rural background concentrations of atmospheric particulates generally originate from non-urban sources thereby their reduction is generally less important as for NO 2 , which is a typical urban pollutant. Similar results were also presented in a similar study reported for the European continent during the spring 2020 lockdown period (Zerefos et al, 2020 ).
Fig.
…”
Section: Resultssupporting
confidence: 91%
“…The lockdown period started in most European cities (including Athens) during March 2020 and lasted mainly up to June 2020 [46]. During this period, air traffic was nearly canceled and car traffic and other means of ground transportation, as well as industrial activities, were minimized on a European level; therefore, air pollution levels in most European cities showed very low concentrations (e.g., a reduction in NO2 by 32% in Athens; see also Figure A1, by 48% in Madrid and by 57-61% in Milan [45,47,[52][53][54][55][56][57]). Similarly, an air pollution level reduction was also observed in many cities all over the world (Canada, Brazil, India, Cairo, Southeast Asia, etc.)…”
Section: Introductionmentioning
confidence: 98%
“…2020 and 2021 were characterised by notable climatic extremes, creating substantial interest in the intersection of the COVID-19 pandemic with climate risks. Research to date has investigated lessons learned from COVID-19 for climate policy, 10 , 13 , 14 , 15 disaster preparedness, 16 , 17 and support for climate action; 18 , 19 compared the politics of responding to COVID-19 with the politics of responding to climate change; 20 examined implications of the pandemic for greenhouse gas emissions 21 , 22 and the environment as a whole; 23 , 24 and focused on how to improve the sustainability of recovery packages to fulfil the UN Build Back Better campaign goals. 25 , 26 , 27 Studies have also focused on the associations between weather and COVID-19 transmission and, to a lesser extent, the ways climatic factors affect lived experience of and response to COVID-19.…”
Section: Introductionmentioning
confidence: 99%